Implementasi Penilaian 13 Komponen Sumber Daya Manusia (SDM) Budaya Unggul Polri pada Personil Kepolisian Resor (POLRES) Jayapura - Arif Simare Mare; Muhlis Hafel; Yosephina Ohoiwutun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the implementation of the assessment of 13 components of superior POLRI cultural human resources at POLRES Jayapura and what factors support and inhibit the implementation of the Implementation of the policy of assessing 13 components of superior POLRI cultural human resources at POLRES Jayapura. This study adopts a qualitative method. Data collected through interview distribution techniques. Data analysis techniques using the help of the N-Vivo application consist of word frequency, coding comparison diagrams, data presentation, drawing conclusions and checking validity, compiling conclusions and data validity. The results of the study prove that the factors that influence the success of the implementation of 13 components of superior Polri culture, the current level of implementation success is not optimal due to the lack of concern from personnel and personnel have the perception of feeling interfered with by the assessment of 13 components through real-time applications but they admit that application-based performance assessments are objective so they feel that the system is fair and can inhibit corruption in the Polri. Furthermore, supporting factors from work facilities and organizational climate as supporters of the realization of the implementation of the assessment of 13 components of Superior Human Resources of the Indonesian National Police, inhibiting factors consist of excessive work autonomy and gaps in insight between one personnel and another, as supporters of the realization of the implementation of the assessment of 13 components of Superior Human Resources of the Indonesian National Police. Keywords: superior culture of the Indonesian National Police, implementation of assessment, 13 components of Human Resources.